Brain-Derived Neurotrophic Factor and Antidepressive Effect of Electroconvulsive Therapy: Systematic Review and Meta-Analyses of the Preclinical and Clinical Literature. - M Polyakova; M L Schroeter; B M Elzinga; S Holiga; P Schoenknecht; E R de Kloet; M L Molendijk (PLoS ONE, 2015)
Emerging data suggest that Electro-Convulsive Treatment (ECT) may reduce depressive symptoms by increasing the expression of Brain-Derived Neurotrophic Factor (BDNF). Yet, conflicting findings have been reported. For this reason we performed a systematic review and meta-analysis of the preclinical and clinical literature on the association between ECT treatment (ECS in animals) and changes in BDNF concentrations and their effect on behavior. In addition, regional brain expression of BDNF in mouse and human brains were compared using Allen Brain Atlas. ECS, over sham, increased BDNF mRNA and protein in animal brain (effect size [Hedge's g]: 0.38-0.54; 258 effect-size estimates, N = 4,284) but not in serum (g = 0.06, 95% CI = -0.05-0.17). In humans, plasma but not serum BDNF increased following ECT (g = 0.72 vs. g = 0.14; 23 effect sizes, n = 281). The gradient of the BDNF increment in animal brains corresponded to the gradient of the BDNF gene expression according to the Allen brain atlas. Effect-size estimates were larger following more ECT sessions in animals (r = 0.37, P < .0001) and in humans (r = 0.55; P = 0.05). There were some indications that the increase in BDNF expression was associated with behavioral changes in rodents, but not in humans. We conclude that ECS in rodents and ECT in humans increase BDNF concentrations but this is not consistently associated with changes in behavior.